2023
DOI: 10.1002/oby.23641
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Entrainment Signal Regularity Index and associations with children's changes in BMI

Abstract: Objective: This study examined the validity of a novel metric of circadian health, the Entrainment Signal Regularity Index (ESRI), and its relationship to changes in BMI during the school year and summer. Methods: In a longitudinal observational data set, this study examined the relationship between ESRI score and children's (n = 119, 5-to 8-year-olds) sleep and physical activity levels during the school year and summer, differences in ESRI score during the school year and summer, and the association of ESRI s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The authors concluded that nightly deviations in both the timing and duration of sleep in adolescents related to adverse metabolic outcomes, and they put forth important next steps to elucidate the direct and indirect effects of night‐to‐night variability in sleep duration and irregularity of sleep timing. Building on aspects of that review, Moreno and colleagues developed and validated a novel approach to modeling intraindividual temporal trends in circadian regularity by using information on light exposure and activity from a wearable device to calculate the Entrainment Signal Regularity Index (ESRI) [29]. The authors postulated that the ESRI may be better suited than other measures of sleep regularity to capture health effects of less granular, more systematic deviations in sleep schedules over time.…”
Section: Sleep Timing and Regularity As Predictors Of Metabolic Healt...mentioning
confidence: 99%
“…The authors concluded that nightly deviations in both the timing and duration of sleep in adolescents related to adverse metabolic outcomes, and they put forth important next steps to elucidate the direct and indirect effects of night‐to‐night variability in sleep duration and irregularity of sleep timing. Building on aspects of that review, Moreno and colleagues developed and validated a novel approach to modeling intraindividual temporal trends in circadian regularity by using information on light exposure and activity from a wearable device to calculate the Entrainment Signal Regularity Index (ESRI) [29]. The authors postulated that the ESRI may be better suited than other measures of sleep regularity to capture health effects of less granular, more systematic deviations in sleep schedules over time.…”
Section: Sleep Timing and Regularity As Predictors Of Metabolic Healt...mentioning
confidence: 99%